Health‐related quality of life and metabolic control in immigrant and Italian children and adolescents with type 1 diabetes and in their parents. Issue 6 (31st May 2020) - Predieri, Barbara; Bruzzi, Patrizia; Bigi, Elena; Boncompagni, Alessandra; Bocchi, Federica; Cenciarelli, Valentina; Madeo, Simona F.; Poluzzi, Silvia; Pugliese, Marisa; Toffoli, Carlotta; Lucaccioni, Laura; Iughetti, Lorenzo
Abstract: Objective: To determine if the diabetes‐specific health‐related quality of life (D‐HRQOL) of young people with type 1 diabetes (T1D) and their parents is influenced by migrant status. Subjects and Methods: One hundred and twenty‐five patients (12.4 ± 3.55 years, males 53.6%) with T1D and their parents (102 mothers, 37 fathers) were enrolled and categorized into: group A (both foreign parents) and group B (both native Italian parents). The Pediatric Quality of Life Inventory™ 3.0 Diabetes Module (PedsQL™ 3.0 DM) was used to evaluate the D‐HRQOL. Data on diabetic ketoacidosis (DKA) at T1D onset, insulin therapy, and glycosylate hemoglobin (HbA1c) were also collected. Results: Group A (n = 40), compared to group B (n = 85), had higher frequency of DKA at T1D onset ( P < .001) and a lower use of sensor augmented insulin pump ( P = .015). HbA1c values were higher in group A than in group B ( P < .001). Patients' " Diabetes symptoms " ( P = .004), " Treatment barriers " ( P = .001), and " Worry " ( P = .009) scales scores were lower in group A than in group B. Mothers of group A had lower scores in " Diabetes symptoms " ( P = .030), " Treatment barriers " ( P < .001), " Treatment adherence " ( P = .018), " Communication " ( P = .009) scales, and total score ( P = .011) compared to the group B ones. High PedsQL™ 3.0 DM was significantly associated with being Italian, being prepubertal, and having lower HbA1c mean levels. Conclusions: Being a migrant confers disadvantages in terms of D‐HRQOL and metabolic control in children and adolescents with T1D. Specific educational interventions should be considered in the clinical care of patients with migration background, to improve D‐HRQOL and health status.